2020
DOI: 10.4103/jfmpc.jfmpc_881_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oromucosal lesions in HIV positive patients receiving haart-A prospective clinical study

Abstract: Aim: To determine the preponderance of oral mucosal lesions and conditions in patients receiving highly active antiretroviral therapy (HAART) for Human Immunodeficiency virus (HIV). Material and Methods: Patient tested Seropositive for HIV and on HAART therapy were clinically examined to evaluate prevalence of oral lesions. Results: In the pool of 152 HIV positive patients in the study, age ranged from 7 to 71 years, 67 were males and 85 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
3
5
1
Order By: Relevance
“…Oral lesions are the first indicators of HIV infection and progression to AIDS. Although studies suggested that the introduction of new antiretroviral therapies contributes to the decrease of oral lesions 7 , 11 , 14 , 16 , 20 , 21 , 22 , 23 , 24 , the data of this study verified that the associated oral manifestations with HIV patients remain present even in the HAART era. However, it must be observed that ART therapy (mono, dual, and HAART) contributed to a decrease of oral lesions, independently of therapy.…”
Section: Discussioncontrasting
confidence: 40%
See 4 more Smart Citations
“…Oral lesions are the first indicators of HIV infection and progression to AIDS. Although studies suggested that the introduction of new antiretroviral therapies contributes to the decrease of oral lesions 7 , 11 , 14 , 16 , 20 , 21 , 22 , 23 , 24 , the data of this study verified that the associated oral manifestations with HIV patients remain present even in the HAART era. However, it must be observed that ART therapy (mono, dual, and HAART) contributed to a decrease of oral lesions, independently of therapy.…”
Section: Discussioncontrasting
confidence: 40%
“…Periodontal disease with or without mobility were the predominant oral lesions in the patients of this study. Even in patients with HAART therapy, periodontal disease was also observed, which is a high value compared to other similar studies 7 , 12 , 21 , 27 , 28 . The results also indicate a relation between age, smoking, and duration of treatment with periodontal disease with mobility.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations